2021
DOI: 10.1002/cbdv.202000863
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Probe into the Dual Inhibition of T. cruzi Glucokinase and Hexokinase in Chagas Disease Treatment – A Stone Killing Two Birds?

Abstract: Glucokinase (GLK) and Hexokinase (HK) have been characterized as essential targets in Trypanosoma cruzi (Tc)‐mediated infection. A recent study reported the propensity of the concomitant inhibition of TcGLK and TcHK by compounds GLK2‐003 and GLK2‐004, thereby presenting an efficient approach in Chagas disease treatment. We investigated this possibility using atomic and molecular scaling methods. Sequence alignment of TcGLK and TcHK revealed that both proteins shared approximately 33.3 % homology in their gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 73 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…We arrive to this conclusion since it is already known that T. brucei hexokinase I is a validated therapeutic drug target [36] and the T. brucei hexokinase isoenzymes most likely share a high degree of three-dimensional structural similarity to TcHxK. Moreover, the virtual three-dimensional structural work by Omolabi and colleagues, in which they contended a theoretical binding site for two 3-nitro-2-phenyl-2H-chromene analogues on TcHxK [30], seems reasonable. However, we believe that in order to move forward, their computational work should be investigated experimentally to validate their binding site hypothesis.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…We arrive to this conclusion since it is already known that T. brucei hexokinase I is a validated therapeutic drug target [36] and the T. brucei hexokinase isoenzymes most likely share a high degree of three-dimensional structural similarity to TcHxK. Moreover, the virtual three-dimensional structural work by Omolabi and colleagues, in which they contended a theoretical binding site for two 3-nitro-2-phenyl-2H-chromene analogues on TcHxK [30], seems reasonable. However, we believe that in order to move forward, their computational work should be investigated experimentally to validate their binding site hypothesis.…”
Section: Discussionmentioning
confidence: 65%
“…For the TcGlcK binding site, they showed that compounds 1 (GLK2-003) and 9 (GLK2-004) had an affinity to interact with residues P92 and T185, which were found near the D-glucose binding site, as visualized in the solved X-ray crystal structure of TcGlcK first reported by Cordeiro and colleagues [33]. They also pointed out that in TcHxK, residues of interest were P163 and T237, which were also found near the D-glucose binding site [30]. Compounds 1 and 9 would be considered as competitive inhibitors in this case; however, our study showed a different outcome.…”
Section: T Brucei Biological Assaymentioning
confidence: 83%
See 2 more Smart Citations